Treated knitted fabric for hip-protective pads for elderly women, part I: force attenuation capacity. Issue 8 (April 2019) - Wardiningsih, Wiah; Troynikov, Olga
This paper describes a study of hip-protective pads made from warp-knitted spacer fabric treated with shear thickening fluid (STF). Hip fractures, mostly caused by falls, are a substantial contributor to morbidity and mortality in the elderly, and incidence is rising worldwide. Hip-protective pads reduce fractures, but wearing adherence is poor. Protective pads made from breathable and comfortable fabrics can improve adherence and prevent more hip fractures. In this research, warp-knitted spacer fabrics were treated with STF using different methods. Treatment 1 involved STF and room-temperature vulcanizing silicone, while treatment 2 applied STF and tetraisopropyl titanate. The effects on force attenuation capacity of each treatment method, the amount of STF used, and fabric layering were measured using drop impact tests. Treated knitted spacer fabric had significantly higher force attenuation capacity than untreated knitted spacer fabric. Impact forces decreased as the number of layers increased and as STF concentrations rose. Treatments 1 and 2 produced fabrics with force attenuation capacity similar to that of closed-cell foam.